Dual processing streams in chemosensory perception - Frasnelli, Johannes; Lundström, Johan N.; Schöpf, Veronika; Negoias, Simona; Hummel, Thomas; Lepore, Franco (Frontiers in Human Neuroscience, 2012)
Higher order sensory processing follows a general subdivision into a ventral and a dorsal stream for visual, auditory, and tactile information. Object identification is processed in temporal structures (ventral stream), whereas object localization leads to activation of parietal structures (dorsal stream). To examine whether the chemical senses demonstrate a similar dissociation, we investigated odor identification and odor localization in 16 healthy young subjects using functional MRI. We used two odors (1. eucalyptol; 2. a mixture of phenylethanol and carbon dioxide) which were delivered to only one nostril. During odor identification subjects had to recognize the odor; during odor localisation they had to detect the stimulated nostril. We used General Linear Model (GLM) as a classical method as well as Independent Component Analysis (ICA) in order to investigate a possible neuroanatomical dissociation between both tasks. Both methods showed differences between tasks - confirming a dual processing stream in the chemical senses - but revealed complementary results. Specifically, GLM identified the left intraparietal sulcus and the right superior frontal sulcus to be more activated when subjects were localising the odorants. For the same task, ICA identified a significant cluster in the left parietal lobe (paracentral lobule) but also in the right hippocampus. While GLM did not find significant activations for odor identification, ICA revealed two clusters (in the left central fissure and the left superior frontal gyrus) for this task. These data demonstrate that higher order chemosensory processing shares the general subdivision into a ventral and a dorsal processing stream with other sensory systems and suggest that this is a global principle, independent of sensory channels.